Попередження правозастосовчих помилок - Прус, Е. У.; Prus, E. (My University, 2013)
The article is dedicated to the highlights of state activity on the prevention enforcement mistakes by law enforcement authorities and court of Ukraine. There is the mechanism of the state in the context of ensuring the correct and unmistakable application of the law in the article.
Прус Е. У. Попередження правозастосовчих помилок / Е. У. Прус // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2013. – Т. 13. – С. 581-587.
Keywords: механізм держави; політика попередження помилок; профілактика вчинених помилок; механизм государства; политика предупреждения ошибок; профилактика совершившихся ошибок; mechanism of state; policy to prevent mistakes; prevention of committed mistakes